Jurnal Manajemen - Gunawan, Iba; haerani, anggi; Hidayati, Rizqiyana (Universitas Banten Jaya, 2024)
This research aims to determine the effect of population on open unemployment, determine the effect of the minimum wage on the unemployment rate, and to determine the effect of population and minimum wages on the unemployment rate. This research uses a quantitative method, namely where the data used in this research is in the form of numbers. The type of method used in research is descriptive research. The term in this research is that the researcher does not change, add or manipulate the object or area of research. The results of data analysis show that variable The minimum wage The population and minimum wage have an effect together (simultaneously). This can be seen from the fcount which is greater than the ftable (18,962 > 5,786).